The Role of Village Government in Digital-Based Community Empowerment in Tourism Villages - Setiawan, Agustina (Journal of Governance, 2024)
Community empowerment is one of the keys to success in developing tourist villages. The role of village government and the use of digital technology are important factors in this empowerment effort. This research aims to analyze the role of village government in digital-based community empowerment in tourist villages, identify supporting and inhibiting factors, and evaluate the implementation of digital technology in the empowerment process. This research uses a qualitative method with a descriptive approach, where data is collected through in-depth interviews, field observations, and documentation studies. The research results show that digital-based community empowerment in tourist villages requires the active role of village government in developing digital infrastructure, implementing digital literacy training, and facilitating promotion and marketing. The keys to success include access to technology, digital literacy, active support from the village government, community participation, and availability of resources and funding. Through collaboration with external parties and the use of technology for public services, villages can increase competitiveness, community welfare, and support equitable national development.